Material Requirement Planning Analysis in Micro, Small, and Medium Enterprise. Case Study: Grooveline - An Apparel Outsourcing Company - Iasya, Ade; Handayati, Yuanita (Journal of Business and Management, 2015)
Abstract- Micro, Small, and Medium Enterprise (MSME) is the largest business executor to the Indonesia’s national Product Domestic Bruto (PDB). It contribute 59.8% to the total of PDB, according to the government data related to MSME period 2011-2012. Due to the size of the company, it is inevitable that MSME required to have an efficient workflow and material purchasing in order to minimize the costs and create a better margin in profit. MSME in fashion industry is one of the most promising business ventures, an apparel outsourcing called Grooveline is one of those. Grooveline is a company which offer the service of T-shirt manufacturing that can be ordered according to customer’s wishes in term of design, color, image to be printed, fabrics, and size. Based on the interview with the company’s owner and manager, it was obtained that it is important for Grooveline apparel outsourcing company to be able to fulfil their customer’s demand. These objective, however, inhibited by the problem of the company’s inability to determine what materials should be purchased and how much the need is, and the problem of the company’s inability to make a production planning in order to fulfill the customer demand in the right amount and on the right time.Thus, a calculation of Material Requirement Planning (MRP) of each product produced is crucial to the business in order to design an effective purchasing order. The implementation of the aforementioned plan shall prevent the company from wasting materials and to conduct a more effective production and lead a more profitable business. The requirement that need to be met in order to make a calculation of MRP, are the availability of product structure, Master Production Schedule, Bills of Material, purchasing and production lead time, a time phased structure, Gross Material Requirement, a lot sizing and net material requirement. The final calculation of MRP requirement are being totaled and being compared to the actual purchasing data that the company has performed to satisfy the previous demand. This action is conducted in order to show how much efficiency the company can create when performing MRP from the beginning of period. Result of the total calculation has shown that if company has implemented MRP from the beginning, company can save the amount of Rp 4,459,500,- in price and make saving of 11%. Keywords: Cost Efficiency, Apparel Outsourcing, Material Requirement Planning, Micro, Small and Medium Enterprises (MSME)